2021
DOI: 10.1021/acssensors.0c01719
|View full text |Cite
|
Sign up to set email alerts
|

Engineering a Smart Nanofluidic Sensor for High-Performance Peroxynitrite Sensing through a Spirocyclic Ring Open/Close Reaction Strategy

Abstract: Peroxynitrite (ONOO − ) is an important reactive oxygen/nitrogen species that participates in a range of physiological and pathological processes by modulating ion flux through biological channels. Inspired by a ONOO − -regulated K + channel in vivo, herein, we describe the construction of a smart ONOO −driven nanosensor using a spirocyclic ring open/close reaction approach. The prepared nanosensor possessed a prominent ONOO − selectivity and sensitivity and rapid response (∼90 s) owing to the specific reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…In this system, pillar[ n ]arenes are a new generation of macrocyclic hosts with the advantage of rigid pillar‐ shaped skeleton, easy modification and versatile functionality, which can be used as molecule platform. [ 30‐33 ] First of all, the chiral host was designed and synthesized on the basis of three traits: (1) N ‐acetylcysteine enantiomers as chiral source was introduced into the rims of pillar[6]arene for recognition of R ‐adrenaline; (2) the cavity of pillar[6]arene can include R ‐adrenaline guest by the formation of host‐guest complex; (3) the carboxyl groups as a fixed unit would endow chiral host with stable immobilization on silicon surface by condensation reaction. Secondly, the two forms of chiral surface were fabricated and characterized by X‐ray photoelectron spectroscopy (XPS), contact‐angle test (CA) and circular dichroism spectrum (CD).…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…In this system, pillar[ n ]arenes are a new generation of macrocyclic hosts with the advantage of rigid pillar‐ shaped skeleton, easy modification and versatile functionality, which can be used as molecule platform. [ 30‐33 ] First of all, the chiral host was designed and synthesized on the basis of three traits: (1) N ‐acetylcysteine enantiomers as chiral source was introduced into the rims of pillar[6]arene for recognition of R ‐adrenaline; (2) the cavity of pillar[6]arene can include R ‐adrenaline guest by the formation of host‐guest complex; (3) the carboxyl groups as a fixed unit would endow chiral host with stable immobilization on silicon surface by condensation reaction. Secondly, the two forms of chiral surface were fabricated and characterized by X‐ray photoelectron spectroscopy (XPS), contact‐angle test (CA) and circular dichroism spectrum (CD).…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Chiral OMS with open nanochannels may be synthesized according to the following approaches: (i) direct synthesis by using chiral templates , and (ii) post-modification of the achiral OMS with chiral molecules. Compared with the former, the methods of post-modification are simple, inexpensive, and can maintain the order degree of nanochannels, eventually, the choice of chiral selectors also plays a key role. Including the supramolecular host in the designed chiral selector will increase the selectivity and sensitivity of the nanochannels through establishing the comparatively strong multiple noncovalent interactions with one enantiomer. Jiang et al reported the chiral recognition of an essential amino acid by a β-cyclodextrin-modified nanochannel .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the complexity and fragility of the cell membrane channel in vitro severely obstructed the simulation of GSH transport. Recently, the introduction of artificial solid-state nanochannels offers a possibility to solve the limitations of natural cell membrane channels. The artificial nanochannel, with the aims to obtain a similar function by imitating cell membrane channels, has attracted wide attention due to various merits, such as high stability, adjustable size/channel shape, and flexible modification. Based on artificial nanochannel platforms, various vital physiological processes and biological functions (e.g., identification, transportation, and gating) can be well imitated from their bio-counterparts. For better control on the transport behavior of ions and molecules, the most commonly adopted strategy is to functionalize the nanochannel with suitable ligands. So far, the covalent or noncovalent modification strategies have been broadly utilized to fabricate the pioneering examples of biomimetic nanochannels that can regulate the identification and transportation of specific molecules/ions. Despite this major progress, it is still a nontrivial task to maintain the balance between selectivity/efficiency and reversibility/recyclability for the ion and molecule transmission. Thus, these challenges promoted the design of new strategies to endow the bionic nanochannels with high performance and controllability for precise regulation on the ion/molecule transport.…”
Section: Introductionmentioning
confidence: 99%